Assessment of Level of Knowledge and Practice of Nursing and Midwifery Students on HIV Post Exposure Prophylaxis in Hawassa University, Ethiopia - Endalew Gemechu Sendo (Journal of HIV for Clinical and Scientific Research - Peertechz Publications, 2014)
Background: Nurses, midwives and other health care workers are at risk from Human Immunodeficiency Virus (HIV) and other blood borne infections in the workplace. Post exposure prophylaxis of HIV is the only way to reduce risk of HIV after potential exposure to needle pricks, blood and body fluids. Objectives: The objective of this study is to assess the level of knowledge and practice of nursing and midwifery students regarding post exposure prophylaxis for HIV in Hawassa University, College of Medicine and Health Science in Ethiopia Methods: Institution- based cross-sectional descriptive study was conducted from October to December 2013. A total of 185 students (comprising of 136 nursing and 49 midwifery) who were eligible for the survey were involved in the study. Data was collected using pretested self-administered questionnaires. Data was entered and analyzed by Statistical package for Social Science (SPSS) version 20. Associations of selected variables with HIV PEP use were assessed using chi-square test. A p-value of <0.05 has been considered as statistically significant. The results were presented in frequency tables and percentages. Results: A total of all 185 students belonging to 2rd, 3rd and 4th years of nursing / midwifery students participated in the survey. The mean age of respondents was 21.04 ± 1.59 years. Among all of the respondents, 54 (29.2) were exposed to HIV risky conditions and of these exposed respondents, the most 32(59.3%) started PEP. The main reasons reported as a cause of exposure to HIV risk conditions in the work place were; lack of protective barriers 43 (79.7%) followed by lack of knowledge on standard precautions 10 (18.5 %). Students of final year were more likely to Practice PEP (p=0.01) as compared to students studying in 2nd year and 3rd year. However, post exposure prophylaxis use was not  associated with gender and professional category (P>0.05) Conclusion and Recommendations: The present study revealed that the level of knowledge and practice of Nursing and midwifery students regarding post-exposure prophylaxis against HIV was inadequate. Accessible PEP centre with proper guideline is recommended so that their practice towards utilization of PEP can be enhanced.